Correlation between Dimension of Fingers Phalannx Proximal and Height in the Age of 18-45 Years Old - Talitha Lailatul Hafizah; Dedi Afandi; Chunin Widyaningsih; Fajri Marindra Siregar (Berkala Kedokteran, 2020)
Abstract: Height is one of the data needed in forensic identification process of a remains that is difficult to identify in an incomplete condition. Height estimation can be determined by the proximal phalanx of the fingers which are long bones. This study was conducted on 113 men and 125 women in several places in Riau Province age 18 - 45 years. The height and dimensions of the proximal phalanx of the fingers are measured to get the correlation and linear regression formula for height. There are 6 dimensions measured on the fingers of the left and right hand. The study design was cross sectional. The statistical test used is Pearson correlation to determine the correlation between dimensions of the proximal phalanx on fingers with height and linear regression analysis for height regression formula. The results show that some dimensions of the proximal phalanx of the fingers are significantly correlated with height. Keywords: identification, height, dimensions of the proximal phalanx bone fingers, correlation, regression formula.